Leadership for follower commitment - Cooper, David J. (David John), 1950-; ScienceDirect eBooks (Oxford ; Boston : Butterworth-Heinemann, 2003)
This text challenges management to adopt an approach that is conducive to improved employer/employee relations, and that will enhance the organizations ability to learn and compete within a knowledge-based economy. Practical measures and behaviour viewed as appropriate in an industrial, commercial, and public sector setting are discussed, analysed, and offered as good practice. Leadership for Follower Commitment provides: *research based case studies *a linking of theory, research, and practical managerial experience *an emphasis on psychological forces, employee motivation and perceptions of management action This text is invaluable to students studying Organizational Behaviour, Business (Occupational) Psychology, Human Resource Management, and Human Resource Development at both undergraduate and MSc/MBA level. It is central to Professional / executive development courses. * Enables tutors to concentrate on the recognized and current key dynamics of the leader/worker relationship * Provides a critical examination of the association between leadership and commitment * Issues that stimulate classroom debate and personal reflection are highlighted in the conclusions of each chapter.
Introduction, rationale, national and international environmental analysis; Managers and Leaders; Leadership and employee commitment; Learning from action; Employee commitment and leadership theory revisited.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Leadership; Employee morale; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Employee morale; Leadership; Electronic books